Biology and Population Growth Parameters of Tomato Leaf Miner, (Tuta absoluta, Meyrick) (Gelechiidae: Lepidoptera), on Tomato in the Laboratory - Simkhada, R.; Thapa, R. B. (Journal of Agriculture and Environment, 2019)
Available with full text.